2011
DOI: 10.1007/s00595-010-4440-8
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic diffuse gastric polyposis: Report of a case

Abstract: A 50-year-old woman was admitted because of severe sideropenic anemia. The gastrin levels were within normal ranges. Esophagogastroduodenoscopy showed diffuse gastric polyposis with signs of diffuse oozing. Colonoscopy showed the presence of a 3-cm wide pedunculated polyp of the ascending colon, which was removed by diathermy. The patient was treated by total gastrectomy with Roux-Y esophagojejunostomy. Histological examination showed the presence of diffuse gastric polyposis with the contemporary occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Although the intervening mucosa often demonstrates a Helicobacter -associated chronic gastritis, no architectural distortion nor obvious mucosal oedema is present 69 . Sporadic diffuse gastric polyposis , a recently described entity of uncertain aetiology, is characterised by multiple hyperplastic polyps limited to the stomach but is distinguished by the intimately associated adenomatous lesions 70 . Fundic gland polyps are usually sporadic and multiple, although they may also occur in a syndromic setting (familial adenomatous polyposis and Zollinger–Ellison syndrome) 71–74.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Although the intervening mucosa often demonstrates a Helicobacter -associated chronic gastritis, no architectural distortion nor obvious mucosal oedema is present 69 . Sporadic diffuse gastric polyposis , a recently described entity of uncertain aetiology, is characterised by multiple hyperplastic polyps limited to the stomach but is distinguished by the intimately associated adenomatous lesions 70 . Fundic gland polyps are usually sporadic and multiple, although they may also occur in a syndromic setting (familial adenomatous polyposis and Zollinger–Ellison syndrome) 71–74.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…However, this theory cannot explain the highly localized occurrence of umbilical Endometriosis. 5,6,7 In this case report, our patient had an uncommon case of spontaneous Umbilical Endometriosis, which is endometrial tissue presence in the umbilicus without any history of C-section or any other gynecologic surgeries. The more common form, secondary Umbilical Endometriosis, is caused by implantation of endometrial cells and iatrogenic spreading during laparoscopic or pelvic surgery.…”
Section: Case Reportmentioning
confidence: 80%
“…Another theory suggests that during laparoscopy or through the hematogenous spread, endometrial cells can reach the umbilicus by seeding and may then proliferate. 5 Many theories have been proposed regarding endometriosis etiopathogenesis. Novak has suggested the coelomic metaplasia theory, and Von Recklinghausen has suggested the embryonal rest theory, both of them have indicated that cells come from the Wolffian duct system or coelomic mesothelium have had a transformative change at the cellular level, which subsequently leads to Endometriosis.…”
Section: 4% To 1 % Of All Patients With Extra Pelvicmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric hyperplastic polyposis is a rare, inherited autosomal dominant syndrome, characterized by the presence of ≥50 gastric hyperplastic polyps and often associated with colorectal neoplasm [ 12 , 13 ]. Total gastrectomy with lymphadenectomy is justified in patients with diffuse involvement of the stomach by polyps, which can make detection of a synchronous focus of cancer difficult [ 14 ]. The smaller number of gastric polyps can be treated with endoscopic snare resection, without surgery.…”
Section: Discussionmentioning
confidence: 99%